Roll Out the Red Carpet: Australian Nurses on Screen. Issue 4 (December 2013) - Brigden, Cathy; Milner, Lisa
<x xml:space="preserve">Abstract</x> Cultural connections with caring and femininity have long been associated with the nursing profession, with mainstream media representations often reinforcing stereotypical depictions of nurses. Although more recent mainstream media portrayals increasingly depict nurses as strong, assertive professionals, little research has been conducted into films made by nurses. When nurses take on the filmmaking task, different outcomes are produced, and when their trade union is involved, unionist filmmaking becomes an organizing strategy. This qualitative study, using content and document analysis and interviews, analyzes a selection of films made by, for, and about Australian unionized nurses. We examine a generation of nurse‐made films from the mid‐1980s to the New South Wales Nurses Association's recent innovative efforts. We argue that these films' production and reception not only shifts our understanding about how these (primarily women) workers are represented and represented as organized workers, but also offer new organizing opportunities for their union. We explore the relationships among film, history, gender, and trade unionism, and consider how unions can use film as a mobilizing tool.